Eksistensi Peradilan Agama Pasca Putusan Mahkamah Konstitusi No.93/PUU-X/2012 tentang Penyelesaian Sengketa Perbankan Shariah - Siti Nurhayati (Justicia Islamica, 2015)
Shariah Banking as one of the national banking systems requires various supporting facilities such as legislation. The relevant law that has been enacted to support Shariah Banking is Law Number 21 of 2008 concerning Shariah Banking. In this law, it is explained that religious courts and general courts are authorized to resolve sharia banking disputes. The existence of 2 (two) authorities in this sharia banking dispute into 2 (two) judicial institutions has led to dualism of authority. The inclusion of disputes in the field of sharia banking in the general judicial environment can lead to tangents or conflicts of judicial authority which can result in the absence of order and legal certainty in law enforcement, especially the settlement of sharia banking disputes. The Constitutional Court through Decision Number 93/PUU-X/2012 confirmed that the explanation of Article 52 paragraph (2) of Law Number 21/2008 on Sharia Banking is contrary to the 1945 Constitution and has no binding legal force. It is the explanation of the article that has been the cause of the emergence of choice of dispute resolution (choice of forum). The constitutional consequence is that since the decision, institutions within the Religious Courts are the only judicial institutions authorized to hear sharia banking disputes.